PENGARUH PENDAPATAN ASLI DAERAH, DANA BAGI HASIL DAN LAIN-LAIN PENDAPATAN DAERAH YANG SYAH TERHADAP KINERJA KEUANGAN DI INDONESIA - Muhammad Ali Al Ihsan (Ekonomi Bisnis Manajemen dan Akuntansi (EBMA), 2020)
The purpose of this study is to determine the influence of the local revenue fund, for the results and other local revenue that the shah on the financial performance. The population in this research is Financial statement and budget Report of 34 provinces in the territory of the Unitary State of the Republic of Indonesia with a Purposive Sampling technique where the samples were determined by the criteria of the population of the province numbered above 5.000.000,- the soul in 2020. The Data obtained is a combination of time series and cross section data denganpooling data or combined models. From the results obtained partially each increase of 1 million KK will give rise to the PAD by 83 million, on the contrary will be a decrease in DBH amounted to 39 million and LPDYS 27 million. on the value of statistics in the picture seen is the PAD TO 6.30, DBH -1,27, and LPDYS -0,26 with prob. PAD 0.00, DBH IS 0.21, LPDYS 0,80 it shows that with a significance level of 2% variables influence siqnifikan against KK while the PAD and DBH effect is not significant.